2019
DOI: 10.1186/s13019-019-1024-6
|View full text |Cite
|
Sign up to set email alerts
|

Excessive intravenous crystalloid infusion after video-assisted thoracoscopic surgery lobectomy is associated with postoperative pneumonia

Abstract: BackgroundVideo-assisted thoracoscopic surgery has been widely used in thoracic surgery worldwide. Our goal was to identify the risk factors for postoperative pneumonia in patients undergoing video-assisted thoracoscopic surgery lobectomy.MethodsA retrospective analysis of adult patients undergoing video-assisted thoracoscopic surgery lobectomy between 2016 and 05 and 2017–04 was performed. We used univariate analyses and multivariate analyses to examine risk factors for postoperative pneumonia after lobectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…However, some technical issues were involved in 3 cases, suggesting that this AZM formulation was not inferior to classical prophylactic treatment. A significant relationship was only observed between postoperative pneumonia and heart disease as a comorbidity, which was consistent with previous reports that showed underlying heart disease as a risk factor for postoperative pneumonia (31,33). Although direct correlation between AZM and postoperative pneumonia was not found, the high concentration of AZM in the lung may prevent postoperative pneumonia through an anti-inflammatory effect, as evidenced by the low IL-6 expression in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, some technical issues were involved in 3 cases, suggesting that this AZM formulation was not inferior to classical prophylactic treatment. A significant relationship was only observed between postoperative pneumonia and heart disease as a comorbidity, which was consistent with previous reports that showed underlying heart disease as a risk factor for postoperative pneumonia (31,33). Although direct correlation between AZM and postoperative pneumonia was not found, the high concentration of AZM in the lung may prevent postoperative pneumonia through an anti-inflammatory effect, as evidenced by the low IL-6 expression in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Postoperative pneumonia is one of the most common complications in patients with lung cancer undergoing therapeutic surgical resection and has been reported as a poor prognostic factor (29,30). The reported incidence of postoperative pneumonia following lung cancer surgery ranges from 3.6% to 18.7% (29)(30)(31)(32). The incidence of postoperative pneumonia in our study was 10% (5 cases), while that with traditional cephem antibiotics in our institution was 6.7% to 9.4% between 2013 and 2015 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that 9.15% (145/1,585) of patients suffered from postoperative pneumonia in the Thoracic Perioperative Database for Geriatrics, and 10.30% (17/165) of patients had postoperative pneumonia in the external validation dataset, and these numbers were consistent with other studies. Other studies reported that the prevalence of postoperative pneumonia was 3.6% ( 21 ) to 19.7% ( 15 ). This variation possibly could be explained by the population heterogeneity: the variety of age, different procedures, and diverse inclusive criteria.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have pointed out that some variables were associated with postoperative pneumonia among lung cancer patients after surgery ( 14 , 15 , 22 33 ). More explicitly, in 2015, Simonsen et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation